Functional Properties and Potential Applications of Wheat Bran Extracts in Food and Cosmetics: A Review of Antioxidant, Enzyme-Inhibitory, and Anti-Aging Benefits - Kaori Kobayashi; Md Suzauddula; Ryan Bender; Cheng Li; Yonghui Li; Xiuzhi Susan Sun; Weiqun Wang (Foods)
This review examines existing studies on wheat bran extracts (WBEs) to provide an overview of their functional properties, including antioxidant and enzyme-inhibitory activities, highlighting their potential as natural alternatives for applications in both the food and cosmetic industries. Despite variations in extraction techniques, WBEs consistently demonstrated a significant presence of phenolic compounds and antioxidant activity. In the food industry, WBEs are valued for their nutritional richness, including dietary fiber, proteins, and bioactive compounds such as arabinoxylans. These compounds improve food texture, stability, and baking properties. Additionally, WBEs have demonstrated antimicrobial potential, enhanced product quality, and serve as natural preservatives. Furthermore, WBEs exhibit significant inhibitory effects against collagenase and elastase, suggesting promising anti-aging potential. In the cosmetics sector, WBEs have gained attention due to their emulsion stability, skin-whitening properties, antimicrobial effects, and antioxidant capacities. They have the potential to enhance the stability of cosmetic emulsions, improve skin hydration, and inhibit enzymes linked to skin aging, positioning WBEs as potentially natural alternatives to synthetic ingredients in skincare and anti-aging products. Our recent pilot study also supports that WBEs enhance antioxidant defenses against oxidative stress in rats, highlighting their potential role in anti-aging interventions. To further elucidate the efficacy and bioavailability of the beneficial bioactive compounds in WBEs for both food and cosmetic applications, more comprehensive in vivo studies are required in the future.